2014
DOI: 10.1039/c4cp00692e
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the electrocatalytic reduction of CO2on metallic silver surfaces

Abstract: The electrochemical reduction of CO2 could allow for a sustainable process by which renewable energy from wind and solar are used directly in the production of fuels and chemicals. In this work we investigated the potential dependent activity and selectivity of the electrochemical reduction of CO2 on metallic silver surfaces under ambient conditions. Our results deepen our understanding of the surface chemistry and provide insight into the factors important to designing better catalysts for the reaction. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
509
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 517 publications
(582 citation statements)
references
References 19 publications
51
509
5
1
Order By: Relevance
“…In contrast to Cu, Ag predominately produces H 2 and CO, with CO Faradaic efficiencies exceeding 90% at an applied potential of -1 V vs RHE. 17,18 Furthermore, the product distribution obtained over Ag is less facet-dependent than that observed over Cu. 17 To illustrate Surface preparation methods can also introduce additional variations in activity and selectivity between samples of the same metal due to the impact that these pretreatments have on 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the purity and distribution of facets at the electrode surface.…”
Section: Benchmarking Electrocatalytic Performancementioning
confidence: 83%
“…In contrast to Cu, Ag predominately produces H 2 and CO, with CO Faradaic efficiencies exceeding 90% at an applied potential of -1 V vs RHE. 17,18 Furthermore, the product distribution obtained over Ag is less facet-dependent than that observed over Cu. 17 To illustrate Surface preparation methods can also introduce additional variations in activity and selectivity between samples of the same metal due to the impact that these pretreatments have on 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the purity and distribution of facets at the electrode surface.…”
Section: Benchmarking Electrocatalytic Performancementioning
confidence: 83%
“…Such a dependence now is understood as Ag (110) binds COOH more strongly than other facets 69. In addition to CO and H 2 as the major products, Jaramillo and co‐workers identified four minor reduction products including formate, methane, methanol, and ethanol 71. They found that H 2 was dominant at low and high overpotentials, while CO overtook H 2 in the medium overpotential region.…”
Section: Electrocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…away from the Ag substrate into the bulk solution (as schematically shown in Fig. 9c) [50]. The absorption of impurities at the surface of the AgCl layer was previously discussed in ''Surface chemistry and composition'' section.…”
Section: Intrinsic and Extrinsic Conductivity Of The Agcl Layermentioning
confidence: 99%
“…The presence of C-based compounds is most likely related to a large extent to the (electro) chemical transformations within the process of anodization (lab air), in the sense that: enhanced surface area of the D sensor, together with the wellknown catalytic activity of Ag toward CO 2 reduction reactions, will bring about not only C-based compounds formation, but also reduction of Ag ? to metallic silver [50].…”
Section: Xps Analysis For Sensors C and Dmentioning
confidence: 99%